Tubercular Pericardial Effusion Complicated by Cardiac Tamponade: A Rare Case Report - Sudhan Devkota; Aparajita Sharma; Mahmud Alam Khan; Niraj Kumar Jaiswal; Manoj Karki; Vikash Sahani (Journal of Universal College of Medical Sciences, 2024)
ABSTRACT Cardiac tamponade is a medical emergency which requires early diagnosis and intervention. Tubercular pericardial effusion is an uncommon manifestation of extra pulmonary TB with cardiac tamponade being even rarer. Here, we have a case of 78-year-male who presented with fever, chest pain and shortness of breath for 4 days. He was in respiratory distress, hypoten- sive along with raised JVP and mufﬂed heart sounds. Echocardiography demonstrated cardiac tamponade for which immediate pericardiocentesis was performed. Pericardial ﬂuid analysis was suggestive of tubercular origin for which ATT and steroids started.